A holistic survey on the use of emerging technologies to provision secure healthcare solutions. (April 2022) - Jagatheesaperumal, Senthil Kumar; Mishra, Preeti; Moustafa, Nour; Chauhan, Rahul
Abstract: Healthcare applications demand systematic approaches to eradicate inevitable human errors to design a framework that systematically eliminates cyber-threats. The key focus of this paper is to provide a comprehensive survey on the use of modern enabling technologies, such as the Internet of Things (IoT), 5G networks, artificial intelligence (AI), and big data analytics, for providing secure and resilient healthcare solutions. A detailed taxonomy of existing technologies has been demonstrated for tackling various healthcare problems, along with their security-related issues in handling healthcare data. The application areas of each of the emerging technologies, along with their security aspects, are explained. Furthermore, an IoT-enabled smart pill bottle prototype is designed and illustrated as a case study for providing better understanding of the subject. Finally, various key research challenges are summarized with future research directions. Graphical abstract: Highlights: The survey provides a deep discussion on the use of: IoT-based secure healthcare solutions for provisioning prominent healthcare applications. 5G services and their secure frameworks for healthcare applications. AI for security enhancement in healthcare systems along with the specific application areas. Big Data analytics for ensuring trustworthy healthcare systems. Emerging technologies for the design and development of smart and secure IoT-pill bottle (Case Study).